‘CHALE SUP’: MOTIVATIONS AND PERCEPTIONS OF PIDGIN ENGLISH USAGE IN A GHANAIAN SENIOR HIGH SCHOOL - Atta-Asamoah, Obed; Asare, Ebenezer; Gyimah Manu, James (International Journal of Humanity Studies (IJHS), 2023)
The English language is used for official purposes and the language in education in Ghana. However, the continuous penetration of Pidgin English (PE) in Ghanaian Senior High Schools (SHS) has been evident in recent times. The paper focuses on the motivations and perceptions of students, in a Senior High School (SHS) in Ghana, on their use of PE in school. It adopts the various motivations and perceptions of students on the use of PE, as identified in the literature, in a questionnaire survey for the responses of the research participants. The study reveals that PE is used as a concealment strategy in students’ conversations against those outside their group, and as a means of solidarity. However, the participants exhibited mixed perceptions of the use of PE in schools. The paper provides insights into PE usage in Ghanaian SHSs.